2013
DOI: 10.1111/jnc.12618
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Characterization of a small molecule inhibitor of the alanine serine cysteine transporter ‐1 (SLC7A10)

Abstract: NMDA receptor hypofunction is hypothesized to contribute to cognitive deficits associated with schizophrenia. Since direct activation of NMDA receptors is associated with serious adverse effects, modulation of the NMDA co-agonists, glycine or D-serine, represents a viable alternative therapeutic approach. Indeed, clinical trials with glycine and D-serine have shown positive results, although concerns over toxicity related to the high-doses required for efficacy remain. Synaptic concentrations of D-serine and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 33 publications
(69 reference statements)
0
34
0
Order By: Relevance
“…14 Interestingly, other compounds in this series, (Table 1, Compounds 8, 10) demonstrated some preference for blocking glutamine transport in the rat cell line. Our most potent compound in the rat cell line (Table 1, Compound 5) also exhibited this preference and blocked ASCT2-mediated glutamine uptake in C6 cells with an IC 50 of 1.3 μM.…”
mentioning
confidence: 89%
“…14 Interestingly, other compounds in this series, (Table 1, Compounds 8, 10) demonstrated some preference for blocking glutamine transport in the rat cell line. Our most potent compound in the rat cell line (Table 1, Compound 5) also exhibited this preference and blocked ASCT2-mediated glutamine uptake in C6 cells with an IC 50 of 1.3 μM.…”
mentioning
confidence: 89%
“…(4) Several small molecule Asc-1-selective inhibitors have been developed with differing mechanisms of action, and recent studies have suggested that inhibition of Asc-1 may paradoxically result in reduced, rather than increased, levels of D-serine. (5)(6)(7) Asc-1 (encoded by SLC7A10 gene) is the "light unit" of a heterodimeric amino-acid transporter (where transport activity takes place), which also contains the "heavy unit" 4F2 cell-surface antigen heavy chain (4F2hc, encoded by the SLC3A2 gene). It is a Na + -independent amino acid transporter with homology to the system L transporter (LAT) family.…”
Section: Introductionmentioning
confidence: 99%
“…(12) We initially sought to identify selective inhibitors of Asc-1 by developing an assay that would support a screen of our full compound collection (~3 M compounds). Although radiolabelled amino acid uptake is a well-tested method for examining transporter function including Asc-1, (5)(6)(7) developing a cell line and an assay detection format robust enough for a miniaturized (1536-well plate based) approach was a significant challenge. We describe a radiotracer uptake screening strategy using whole cells (heterologously expressing Asc-1) adherent to scintillation proximity assay (SPA) beads with [ 35 S]-cysteine as a surrogate for D-serine.…”
Section: Introductionmentioning
confidence: 99%
“…The effective dose of D‐Ser was very high in both humans (30 mg/kg/day) and animals (0.8–1.0 g/kg), and the possibility of off‐target and D‐Ser‐related peripheral side effects are concerns. Thus, selective increases in the extracellular D‐Ser levels in the target brain region are desirable, in which one approach is to inhibit the uptake of D‐Ser into the cells in the brain (Thomsen et al, ; Brown et al, ).…”
mentioning
confidence: 99%